1994
DOI: 10.1177/095646249400500606
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Evaluation of a Prototype Western Blot Confirmatory Test Kit for Syphilis

Abstract: A prototype Western blot kit was evaluated as a confirmatory test for syphilis using 131 sera characterized by other serological tests for syphilis. There were 114 treponemal sera (including 94 cases of early syphilis, 83 of which were untreated) and 17 non-treponemal problem sera (11 gave false positive reactions on screening with the TmpA recombinant antigen enzyme immunoassay (EIA), 3 gave false positive fluorescent treponemal antibody absorbed (FTA-abs) tests, and 3 false positive Captia Syphilis G EIA res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The WB technique based on whole-T. pallidum-cell lysate has been widely used in past years (5,6,10,12,17,28,30,49), and it has been shown to be a reliable confirmatory test (4). Few data are available on the use of recombinant-antigenbased immunoblotting in the diagnosis of syphilis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WB technique based on whole-T. pallidum-cell lysate has been widely used in past years (5,6,10,12,17,28,30,49), and it has been shown to be a reliable confirmatory test (4). Few data are available on the use of recombinant-antigenbased immunoblotting in the diagnosis of syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…The Western blot (WB) method has been used for the last 15 years to investigate the immune response to individual Treponema pallidum antigens in sera from experimentally infected animals (1,16,25,26,43,46) and from humans with naturally occurring syphilis (4,5,6,10,17,28,30,40,47,49). This method has been proposed as a possible alternative to either FTA-ABS or MHA-TP for the confirmation of the serological diagnosis of syphilis.…”
mentioning
confidence: 99%
“…The T. pallidum WB is also used as an alternative confirmatory test to improve sensitivity and specificity, but indeterminate and false-positive reactivity patterns have been reported. 7,8,15,22,[27][28][29] It was reported that there is over 95% agreement between the WB and the FTA-ABS test for clinically defined syphilis specimens. In a study, 10 WB results were compared with TPPA and FTA-ABS tests, and the sensitivity of the WB, TPPA and FTA-ABS were all reported at 100% and the specificity were 100%, 100% and 94.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that detection of antibodies to immunodeterminants with molecular masses of 15, 17, 44.5 and 47kDa (TpN15, TpN17, TpN44.5 and TpN47) are diagnostic for acquired syphilis. The Tp-WB showed a high sensitivity in both, treated and untreated infection (Young et al, 1994). One study found that the 17 kDa antigen have the best combined attributes of sensitivity and specificity for diagnostic of syphilis (George et al, 1998).…”
Section: Westen Blot (Wb) and Immuno-blotmentioning
confidence: 99%